Tinjauan Hukum Pidana Islam Terhadap Perjanjian Sebagai Hukuman - Miska sahri hsb & Dermina Dalimunthe (Jurnal El-Thawalib, 2021)
Theft is a type of crime regulated in positive law in Indonesia, the implementation of the sanctions using the provisions in the Criminal Code (KUHP). However, this is as applies in the life of the people of Mompang Julu Village, Kec. North Panyabungan imposes sanctions for perpetrators of theft based on the Criminal Code as well as customary law as additional penalties for perpetrators of criminal acts of theft.From these problems, the author wants to know how the witness of theft in Mompang Julu Village, Kec. Panyabungan Utara and how the review of Islamic criminal law on additional penalties in cases of theft in Mompang Julu Village, Kec. Panyabungan Utara.The type of research used in this research is field research, namely the preparation of going directly to the field to research a problem, the data used are primary and secondary data, data collection methods are literature study methods, documents, interviews and direct observation. The data collected is analyzed using qualitative descriptive methods that are inductive and deductive, which is an effort to find existing facts and analyze them according to existing library materials.The results of this study state that, 1. the crime of theft in the village of Mompang, Julu, kec. North Panyabungan is settled by positive law based on the provisions of the Criminal Code (KUHP) and customary law in the form of an agreement. 2. Review of Islamic Criminal Law against the agreement as an additional punishment in the criminal case of theft in Mompang Julu Village, Kec. Pangabung Utara is in accordance with its application in the rules of Islamic law, namely there may be additional punishment based on the majority of the opinions of scholars who refer to the hadith of the Prophet SAW in a narration from Bahz bin Hukaim which talks about people who are reluctant to pay camel zakat, and the narration from Amr bin Syu ' disgrace that speaks of someone taking fruit